Proton-irradiation influence on current mirror circuit using verilog-a approach based on experimental SOI FinFET characteristics - De Sousa, Bruna Ramos; Agopian, Paula Ghedini Der [UNESP]; Martino, Joao Antonio (The Electrochemical Society, 2020)
In this work, a simple methodology is proposed to simulate the current mirror circuit based on the triple-gate SOI FinFET experimental data, called lookup table in Verilog-A. It was analyzed the reliability of the model, comparing between experimental and simulated data, with has proven to be reliable. It was also evaluated the performance of the transistor and as well the circuit regarding the efficiency and the gain, for p- and n-types, based on three different fin widths, before and after proton-irradiation.